Ovarian Development and Vitellogenin Gene Expression under Heat Stress in Silkworm, Bombyx mori - Satinath Paul; Bela Keshan (Psyche: A Journal of Entomology)
The present study observed the effect of heat stress on ovarian development, fecundity, and vitellogenin gene expression in silkworm, Bombyx mori. The result showed that the heat shock treatment to spinning larvae and pupae at 39°C (1 h and 2 h) did not cause any adverse effect on the reproductive performance of B. mori. However, the heat shock treatment at 42°C or above caused a decrease in the fecundity. The heat shock treatment to day 2 pupae for 2 h at 45°C caused a drastic effect on the development of ovary as measured by gonadosomatic index. The study thus showed that a brief exposure of Bombyx larvae and pupae to a temperature of 42°C or higher, much prevalent in tropical countries like India, greatly affects the ovarian development and reproductive performance of this commercially important insect. The study further showed a developmental- and tissue-specific expression of vitellogenin mRNA in fat body and ovary upon heat shock. When heat shock treatment was done at 39°C and 42°C to spinning larvae, ovary showed an upregulation in the expression of vitellogenin mRNA, whereas fat body failed to do so. However, at 45°C, both fat body and ovary showed a downregulation. The heat shock treatment to day 2 pupae showed an upregulation in the vitellogenin mRNA expression in both fat body and ovary, even at 45°C. The upregulation in the expression of vitellogenin upon heat shock indicates its role in thermal protection of Bombyx larvae and pupae.